Sustainable Waste Management Policy in Sleman Regency - Dea Hafiz Finiagara Putra; Rijal Ramdani; Mada-o Puteh; Mukhrijal (Journal of Governance and Social Policy, 2025)
This paper aims to examine sustainable waste management policies in Sleman Regency based on the types a distributive, regulative, and redistributive policies. Meanwhile, the method used in this research is descriptive qualitative. The research results show that the waste management policy in Sleman Regency, when viewed from the types of policies, namely distributive, regulative, and redistributive, is based on Local Regulation No. 6 of 2023 concerning the policies of Waste Management, has regulated waste management systematically and sustainably, including reducing waste at the source. For disruptive policies, various infrastructure facilities and infrastructure have been built for waste management and to encourage active community participation. Meanwhile, for redistributive policies, the Sleman local government has regulated it in Local Regulation No. 9 of 2018 concerning Retribution for Waste, where, in this regulation, the amount and sanctions for the community and business actors, and agencies are regulated. This research concludes that sustainable management policies based on existing policies have been regulated in a systematic and sustainable manner, but there needs to be internal strengthening related to efforts to encourage better waste awareness and community participation by conducting widespread outreach and campaigns.